CORPORATE IDENTITY VISUAL DAN CITRA PERUSAHAAN MELALUI FASILITAS RUANG BACA DI BAPUSIPDA JAWA BARAT - Tirayan Agustina; Rachmaniar Rachmaniar (Lembaga Penelitian & Pengabdian Masyarakat Universitas Bina Sarana Informatika, 2014)
Abstract - In the opinion of the public library is a place to store books that are old fashioned or outdated and drab place. With grim reading room, full of dust, stuffy and dark. This negative image of the library in society that drives Bapusipda Jabar, to change the negative image by construct a new building and provide complete facilities for library users This study aims to understand the image of West Java Bapusipda through corporate identity visual